Neobractatin and Trametinib Synergistically Induce Apoptosis and Gasdermin E‐Dependent Pyroptosis in Pancreatic Cancer Cells - Jiaqi Tan; Ziyi Bao; Kai Qin; Liujing Zhu; Changwu Zheng; Jiabin Jin; Li Zhang; Hongxi Xu (MedComm)
ABSTRACT Mutations in mitogen‐activated protein kinase kinase (MEK) are prevalent in pancreatic ductal adenocarcinoma (PDAC), but many MEK inhibitors inadvertently activate protein kinase B (AKT). We propose a promising PDAC treatment strategy by combining the MEK inhibitor trametinib with neobractatin (NBT), a natural compound from Garcinia bracteata. Our results demonstrated that this combination significantly impeded cell growth by inducing gasdermin E (GSDME)‐mediated pyroptosis and apoptosis. GSDME, overexpressed in PDAC tissues and correlated with histological differentiation, underscores the role of pyroptosis in PDAC. RNA‐seq results indicated that the phosphoinositide 3‐kinase/protein kinase B (PI3K/AKT) pathway was the primary target of the combination treatment. Mechanistic studies revealed the combination effectively reduced both total and phosphorylated AKT levels, thereby inhibiting protein kinase B/IκB kinase (AKT/IKK) and protein kinase B/mammalian target of rapamycin (AKT/mTOR) signaling pathways. Additionally, the combination disrupted mTOR complex 2 (mTORC2), preventing the trametinib‐induced AKT activation. MicroRNA sequencing analysis indicated that the combination reduced AKT levels by upregulated miR‐149‐5p. Further research demonstrated that the combination increased intracellular reactive oxygen species (ROS), while N‐acetylcysteine (NAC, a ROS scavenger) reversed the cell growth inhibition and AKT suppression. In vivo, the combination significantly inhibited tumor growth by inducing pyroptosis and apoptosis, outperforming gemcitabine. Our findings provide novel insights into the potential of combining NBT and trametinib to induce pyroptosis and apoptosis through the ROS/AKT/GSDME axis, offering a theoretical basis for future PDAC treatment.